2009
DOI: 10.1007/s11205-009-9520-z
|View full text |Cite
|
Sign up to set email alerts
|

Changing Communities, Community Satisfaction, and Quality of Life: A View of Multiple Perceived Indicators

Abstract: Tourism’s impacts, Community satisfaction, Quality of life, Costa Rica,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 38 publications
1
37
0
3
Order By: Relevance
“…According to Matarrita-Cascante (2010), interaction between residents and tourists promotes the exchange of ideas which can lead to economic and social progress, but as McCool and Martin (1994) should focus on providing jobs and attracting investments into the community, which can benefit resident quality of life. Aref (2011) suggests the strongest tourism impacts are often linked with emotional and community well-being, and income and employment.…”
Section: Resident Satisfaction and Tourism Development Supportmentioning
confidence: 99%
“…According to Matarrita-Cascante (2010), interaction between residents and tourists promotes the exchange of ideas which can lead to economic and social progress, but as McCool and Martin (1994) should focus on providing jobs and attracting investments into the community, which can benefit resident quality of life. Aref (2011) suggests the strongest tourism impacts are often linked with emotional and community well-being, and income and employment.…”
Section: Resident Satisfaction and Tourism Development Supportmentioning
confidence: 99%
“…In addition to rapid growth in energy development, scholars have investigated changing community perceptions and behaviors in a range of other settings such as general rural community change [83][84][85], amenity-based development [86,87], wildland fire management [88,89], and natural or technological disasters [90,91]. Several studies particularly examined the potential causes of temporal community dynamics.…”
Section: Changing Community Perceptions and Actionsmentioning
confidence: 99%
“…Using community-level panel data from 99 small towns across Iowa, researchers participating in the Rural Development Initiative at Iowa State University found that higher perceived social integrity contributed to a smaller decline in community attachment and quality of life [84,85], while community structural factors (e.g., number of farms and town size) were related to local social capital and community involvement [83]. Similarly, Matarrita-Cascante [87] maintained that the effects of tourism-driven changes on community satisfaction and perceived quality of life depended on the socioeconomic and cultural settings of localities.…”
Section: Changing Community Perceptions and Actionsmentioning
confidence: 99%
“…Considered the largest industry in the world, a "driving force" of economic growth, of inclusive development and environmental sustainability [1], tourism represents more than one third of the total value of global trade in services [2]. Most regional tourism plans and policies are based on the idea that tourism is a development option that is desirable for communities [3], as it causes both direct and indirect, positive effects on the economy and the well-being of communities [4], [5], [6], [7], [8], [9], [10], [11]. In the latter part of the 20th century, tourism has become an important sector of economic activity and will continue to grow in the years to come, leading to a diversification of tourism products and destinations [12].…”
Section: Introductionmentioning
confidence: 99%